Chapter 3 D. Natsagdorj, Mongolian travel writing, and ideas about national identity - Marzluf, Phillip (Taylor & Francis, 2021)
In 1927, upon his arrival in Berlin, D. Natsagdorj, one of approximately 45 young Mongolian students who participated in an educational program in Germany and France, composed a long travel poem, "Notes on the Trip to Berlin." Not only does this poem serve as an early example of Natsagdorj's writing, it emphasizes Natsagdorj's role as a didactic writer for the early Mongolian People's Republic, in particular in conveying the values of the cosmopolitan socialist, a modern subjectivity that quite consciously separated itself from the previous aristocratic, Buddhist, and pastoral identities of pre-revolutionary Mongolia. "Notes on the Trip to Berlin" provides a geographical orientation of the new economic and cultural flows from Mongolia to Western Europe through the Soviet Union. Natsagdorj's poem is also significant because it is one of the few examples of Mongolian travel literature and enables Natsagdorj to actively resist the image of Mongolians perpetuated by Western travel writers. From the perspective of Natsagdorj's Mongolian readers, "Notes on the Trip to Berlin" teaches them the process of navigating socialist and pre-revolutionary identities as Natsagdorj grapples with socialist and pre-revolutionary literary forms and language.